ANALYZING COVERT THREATS IN VERBAL COMMUNICATION THROUGH PSYCHOLINGUISTIC AND PRAGMATIC LENSES - Arslanbekova D. Sh. (“SUN’IY INTELLEKTNING TIL O‘RGANISHDAGI O‘RNI” MAVZUSIDA TALABALAR ILMIY-AMALIY KONFERENSIYASI, 2025)
This study delves into the intricate realm of covert threats within verbal communication, employing psycholinguistic and pragmatic frameworks to unravel their underlying mechanisms. Covert threats, often veiled in indirect language and nuanced expressions, pose significant challenges in detection and interpretation. By integrating psycholinguistic analysis, which examines the cognitive processes influencing language production and comprehension, with pragmatic analysis focusing on context-driven meaning and speaker intent, this research aims to identify linguistic markers indicative of concealed threats. The methodology encompasses a comprehensive review of existing literature, coupled with the examination of real-world communication instances where covert threats are prevalent. Findings highlight specific lexical choices, syntactic structures, and discourse patterns that frequently signal underlying threatening intentions. The study underscores the importance of context, speaker-hearer dynamics, and cultural nuances in interpreting such threats. The insights garnered hold substantial implications for fields like forensic linguistics, security analysis, and communication studies, offering tools for more effective identification and understanding of covert threatening language.